Other Means of Grace: Agency, Dependency, and the Loan Libraries of the American Seamen's Friend Society - McCamant, Jane (The Northern Mariner / Le marin du nord, 2025)
This paper assesses the success of the loan libraries of the American Seamen’s Friend Society (ASFS). It contains an analysis of 20 reports submitted to the ASFS by shipboard librarians between 1865 and 1867. Analysis of the reports themselves and how they were represented in ASFS publications reveals the paradoxical relationship the ASFS had with stereotypes of seamen. In the ASFS’s images of sailors and in their administration of the loan libraries, those sailors were kept in a position of moral dependency. The paper concludes by suggesting that Herbert Blumer’s model of social problems as constituted by collective action is a fruitful way to consider seamen’s benevolence in general, and a productive framing to move forward with studies of loan libraries in particular.